Eosinophil Progenitors in Patients With Non-Asthmatic Eosinophilic Bronchitis, Eosinophilic Asthma, and Normal Controls - Zhan, Chen; Xu, Rong; Li, Bizhou; Liu, Jiaxing; Liang, Wanqin; Zhang, Shengfang; Fang, Liman; Zhong, Shuxin; de Silva, S. Dushinka Shaniya Helen; Sivapalan, Dhinesan; Luo, Wei; Li, Jing; et al. (Frontiers in Immunology, 2022)
Objective This study aims to explore the potential of in situ airway differentiation of eosinophil progenitors (EoPs) and hematopoietic progenitor cells (HPCs) in sputum and peripheral blood from patients with non-asthmatic eosinophilic bronchitis (NAEB), eosinophilic asthma (EA), and healthy controls (HC). Methods Using flow cytometry, we enumerated sputum and blood HPCs and EoPs in patients with NAEB (n=15), EA (n=15), and HC (n=14) at baseline. Patients with NAEB and EA were then treated for 1 month with budesonide (200 μg, bid) or budesonide and formoterol (200/6 μg, bid), respectively. HPCs and EoPs in both compartments were re-evaluated. Results At baseline, NAEB and EA both had significantly greater numbers of sputum but not blood HPCs and EoPs (p<0.05) compared to HC. There were no differences between NAEB and EA. After 1 month of inhaled corticosteroid (ICS) treatment, NAEB patients showed a significant improvement in cough symptoms, but the attenuation of sputum HPC and EoP levels was not significant. Conclusions NAEB patients have increased airway levels of HPCs and EoPs. One-month treatment with ICS did not fully suppress the level of EoPs in NAEB. Controlling in situ airway differentiation of EoPs may control airway eosinophilia and provide long-term resolution of symptoms in NAEB.